2012
DOI: 10.1371/journal.pone.0031740
|View full text |Cite
|
Sign up to set email alerts
|

Gastrotricha: A Marine Sister for a Freshwater Puzzle

Abstract: BackgroundWithin an evolutionary framework of Gastrotricha Marinellina flagellata and Redudasys fornerise bear special interest, as they are the only Macrodasyida that inhabit freshwater ecosystems. Notwithstanding, these rare animals are poorly known; found only once (Austria and Brazil), they are currently systematised as incertae sedis. Here we report on the rediscovery of Redudasys fornerise, provide an account on morphological novelties and present a hypothesis on its phylogenetic relationship based on mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 17 publications
3
32
1
3
Order By: Relevance
“…The robustly supported groups include: 1) the densely sampled families Thaumastodermatidae and Turbanellidae and their recognized subgroupings; 2) the recently highlighted alliance between Redudasys fornerise Kisielewski, 1987 and Anandrodasys agadasys (Hochberg, 2003) (Fam. Redudasyidae, see [24]) and their sister-group relationship with a clade composed of Cephalodasys and Dolichodasys (Fam. Cephalodasyidae); and 3) the sister-group relationship between Crasiella Clausen, 1968 and Megadasys Schmidt, 1974, recently united in the family Planodasyidae [33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The robustly supported groups include: 1) the densely sampled families Thaumastodermatidae and Turbanellidae and their recognized subgroupings; 2) the recently highlighted alliance between Redudasys fornerise Kisielewski, 1987 and Anandrodasys agadasys (Hochberg, 2003) (Fam. Redudasyidae, see [24]) and their sister-group relationship with a clade composed of Cephalodasys and Dolichodasys (Fam. Cephalodasyidae); and 3) the sister-group relationship between Crasiella Clausen, 1968 and Megadasys Schmidt, 1974, recently united in the family Planodasyidae [33].…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic analysis of the Macrodasyida based on molecular traits (18S rDNA gene alone or in conjunction with the 28S rDNA and Cox 1 genes) have provided support for some of the traditional groupings based on morphological traits but have also unveiled surprising associations, e.g. congeneric species grouping with different families or morphologically disparate species grouping together (e.g., [24, 43, 44]).…”
Section: Discussionmentioning
confidence: 99%
“…As of December 2017, the group comprises 840 species divided into the two orders Macrodasyida and Chaetonotida (Todaro 2017). Macrodasyida generally includes taxa living interstitially in marine sandy bottoms (but see e.g., Todaro et al 2012), while Chaetonotida comprises species found from marine to freshwater environments. The alpha biodiversity and systematics of the Phylum are changing at a fast pace, as shown by the continuous finding and description of new taxa (for marine taxa, e.g., Hochberg et al 2014, Todaro et al 2014, 2015, Lee and Chang 2017) and the in-group phylogenetic reassessments (e.g., Kånneby et al 2013, Todaro et al 2014, Kånneby and Todaro 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Research teams headed by one of us (MAT) have visited three islands: St. John in the US-Virgin islands, Jamaica, and Curaçao. Part of the information and/or taxa found have appeared in several papers (e.g., Hummon et al 2010, Kånneby et al 2012, 2013, 2014, Todaro et al 2012, Schuster et al 2017). Specifically devoted to the Jamaican survey were two papers dealing with the description a new species of Macrodasys and the description of a new species, genus and family (Todaro and Leasi 2013, Todaro et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A falta de dados sobre essas duas espécies levou os estudiosos a situarem estas espécies como insertae sedis dentro da ordem Macrodasyida. Entretanto, Todaro et al (2012) Garraffoni et al (2010) e Araújo et al (2013), em amostras qualitativas no estado de Minas Gerais, respectivamente, observaram inúmeros espécimes dos gêneros Redudasys e Marinellina.…”
unclassified